The consistency of s2 in the linear regression model when the disturbances are spatially correlated - Butte Gotu (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
Conditions for the consistency of the estimator s2 of the variance of the disturbance a2u under first-order spatial error processes are given.
Keywords: 519; Ordinary least squares; Consistency; Spatial error process; Spatial correlation